Elmira City Charter, Title 3—Powers and Duties of the Common Council, § 26, pts. d, e, & k, ELMIRA, REVISED CHARTER at 17, 20-22 (Elmira, New York) (Gazette Company 1898). - (:unkn) unknown (General Publisher, 1898)
Granted the Common Council the power to regulate firearm dicharge and gun powder storage
--
Keywords: DISCHARGE; GUN POWDER STORAGE